Challenges in diagnosing and treating Polycystic Ovary Syndrome in adolescentes (Research, Society and Development, 2024)
Introduction: Polycystic Ovary Syndrome (PCOS) is one of the most prevalent endocrinopathies in women of childbearing age. Starting in adolescence, the syndrome in this age group presents several challenges from the moment the diagnosis is made to treatment. Methodology The objective of this article is to present a literature review addressing the diagnosis and treatment of PCOS in adolescents. The search was carried out in the PubMed and Google Scholar databases, using descriptors in English and Portuguese, with inclusion criteria for illustrations for studies published in the last 12 years. Conclusion: Diagnosis in adolescence is complicated by the overlapping of symptoms with the normal changes of puberty. In addition, treatment requires a multidimensional approach, including, mainly, changes in lifestyle, together with pharmacological interventions. After analyzing the literature, it was inferred the need to develop specific diagnostic criteria for adolescents, as well as additional studies to improve the management of PCOS.